Saúde e sucesso na vida: a prática discursiva da Herbalife - Silva, Olga Amália da (2015)
The aim of this research is to investigate the functioning of the discursive practices of Herbalife, counted as a global leader in the "wellness industry". We are interested in studying the discursive functioning of these statements that proclains that health individuals who are satisfied with their self-image tend to be happier and to succeed in their personal and professional life. The corpus of the research is composed of discursive sequences collected from the Herbalife website, the catalog available at sales points of the brand products, magazine advertisements and other various genres, circulating in different media, considering for their selection the “Indiciary Paradigm” (GINZBURG, 1991), which proposes to value the evidence, signs, clues that show to be interesting to the analyst in his work of interpretation of the studying phenomenon. The corpus is analyzed from the theoretical assumptions and analytical principles of Discourse Analysis of French origin (AD), especially from its most recent developments. The concepts of ethos and scenography (MAINGUENEAU, 2003, 2012a, 2012b) show to be productive for analysis. It is possible to verify that in Herbalife’s discourse, health – often confused with the ideal of a slim and strong body – is seen as a condition for personal and professional success. In addition, success is presented as a must for the modern man, in this discourse which, among other elements of its operation, is legitimized through a scientific ethos.